2021
DOI: 10.1007/s11109-020-09675-6
|View full text |Cite
|
Sign up to set email alerts
|

Pay Your Debts: Moral Dilemmas of International Debt

Abstract: Should a government repay its international debts even if this imposes severe hardships on its citizens? Drawing on moral psychology, we investigate when people think a government is morally obligated to pay its debts. Participants read about a government that has to decide whether to default on its debt payments or cut vital programs. Across conditions, we varied the number of jobs at stake and whether a full or partial default is required to save them. Overall, most participants judged that a government shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…Moral language may arouse base emotions such as resentment, grievance and rage which, in turn, may fuel populist rhetoric in both creditor and debtor countries. There is indeed evidence indicating that moral judgments can influence individual preferences regarding financial bailouts (Rathbun et al, 2019) and may diminish altruistic motives related to debt repayment (Del Ponte and DeScioli, 2022). Simultaneously, the moral stereotyping of Greece could have played a role in the Greek government's decision to reject the 2015 bailout.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral language may arouse base emotions such as resentment, grievance and rage which, in turn, may fuel populist rhetoric in both creditor and debtor countries. There is indeed evidence indicating that moral judgments can influence individual preferences regarding financial bailouts (Rathbun et al, 2019) and may diminish altruistic motives related to debt repayment (Del Ponte and DeScioli, 2022). Simultaneously, the moral stereotyping of Greece could have played a role in the Greek government's decision to reject the 2015 bailout.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…In turn, this moral discourse may have affected the key actors involved during and even after the crisis. Indeed, there is some evidence suggesting that moral judgments play a role in defining individual preferences toward financial bailouts (Rathbun et al, 2019) and that they can attenuate altruistic motives regarding debt repayment (Del Ponte and DeScioli, 2022). At the same time, the moral stereotyping of Greece may have even played a role in the Greek government's self-damaging decision to repudiate the 2015 bailout.…”
Section: Introductionmentioning
confidence: 99%
“…Deontological moral intuitions have shaped the public's response to political events long before COVID-19. A common theme in this research is the intransigence toward compromise with others on any issue that becomes moralized ( Dehghani et al, 2010 ; Del Ponte and DeScioli, 2022 ; Delton et al, 2020 ; Ginges et al, 2007 ; Ryan, 2014 , 2017 , 2019 ; Skitka and Bauman, 2008 ). For instance, previous work found that people who considered Social Security benefits a moral issue resisted compromises on the issue and were even willing to punish politicians who were in favor of compromise ( Ryan, 2017 ).…”
Section: Moral Obstinacy Regarding Covid-19 Measuresmentioning
confidence: 99%
“…Similarly, Iranian respondents who considered their nuclear program as an absolute moral right met monetary offers to change their minds with more anger ( Dehghani et al, 2010 ). In yet two more studies, American participants judged that a government must repay its international debt even if the consequences of repayment are as much as 20 times worse than defaulting ( Del Ponte and DeScioli, 2022 ). People who hold deontological stances about the response to COVID-19 are similarly irremovable in their convictions ( Prosser et al, 2020 ).…”
Section: Moral Obstinacy Regarding Covid-19 Measuresmentioning
confidence: 99%
“…Revisions to how debt is created and perpetuated, as well as new forms of taxation, would be vital to supporting better lives and health in low-and middle-income countries, and to discouraging wealthy countries from living at the expense of future generations. 56…”
Section: Changing the Economic Paradigm And The Values Guiding Global...mentioning
confidence: 99%